2020
DOI: 10.1186/s12886-020-01614-7
|View full text |Cite
|
Sign up to set email alerts
|

Hole diameter ratio for prediction of anatomical outcomes in stage III or IV idiopathic macular holes

Abstract: Background: To determine whether preoperative hole diameter ratio (HDR) is a predictive factor for postoperative anatomical outcome for stage III or IV idiopathic macular holes (IMHs). Methods: One-hundred and one eyes with stage III or IV IMH were included in this retrospective case series study. All cases were treated with vitrectomy combined with internal limiting membrane (ILM) peeling and room air tamponade. The macular hole (MH) minimum and maximum diameter was measured on preoperative optical coherence … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…Qi et al . [ 21 ] in their study on 101 patients with stage-3 and stage-4 holes found HDR ( P = 0.01) to be significantly different in the two groups (hole closed and un-closed), influencing closure rate with larger holes.…”
Section: Discussionmentioning
confidence: 97%
“…Qi et al . [ 21 ] in their study on 101 patients with stage-3 and stage-4 holes found HDR ( P = 0.01) to be significantly different in the two groups (hole closed and un-closed), influencing closure rate with larger holes.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, HDR primarily represents tangential traction, and eyes with a preoperative HDR value of < 0.6 have a higher chance of achieving type-I closure. [ 11 ] Based on the above understanding, elimination of tractional components following surgery should increase the chances of predominantly type-1 closure. However, some indices such as MHI, THI, and HDR have been found to predict type-1 closure, whereas outer diameter and DHI have been found to predict type-2 closure.…”
Section: Discussionmentioning
confidence: 99%
“…From these values, derived hole indices such as HFF, MHI, THI, and HDR were calculated as described in previous studies. [ 6 7 8 11 ]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations